A Study on Professional Learning Community (PLC) Methods for Enhancing Pre-Service English Teachers' Quality in TPACK - Sari, Valentina Dyah Arum; Binawan, Heribertus (Journal of English Language and Education, 2025)
Developing Technological Pedagogical Content Knowledge (TPACK) is crucial for pre-service English teachers, yet they often lack practical collaboration. This mixed-method study determines the implementation of Professional Learning Community (PLC) practices in fostering TPACK competency and identifies key challenges and best practices in their implementation. Data was collected using a Likert-Scale Questionnaire to measure perceptions of PLC and semi-structured interviews for in-depth experiences. The PLC model proved in building all TPACK components, evidenced by overwhelmingly positive perception scores: Technological Knowledge (TK) and Pedagogical Knowledge (PK) both averaged 94.28, and Content Knowledge (CK) averaged 90.49. This demonstrates increased confidence in integrating digital tools and successfully combining Technology, Pedagogy, and Content. The most successful practices identified were real-world application, structured group reflection, and professional guidance. However, the study identified the challenges, primarily related to time constraints for discussions and the need for improved post-session support. Furthermore, the PLC is a highly successful model for holistic TPACK development. By addressing the minor issues related to session timing and support, the already effective program can be further optimized for better success in transferring competencies to the classroom.